2006
DOI: 10.1088/0957-4484/17/16/029
|View full text |Cite
|
Sign up to set email alerts
|

Silica coated, water dispersible and photoluminescent Y (V,P)O4:Eu3+,Bi3+nanophosphors

Abstract: We propose an approach for silica encapsulation of YV((0.7))P((0.3))O(4):Eu(3+), Bi(3+) nanophosphors through a microemulsion process. The resulting YV((0.7))P((0.3))O(4):Eu(3+), Bi(3+)@SiO(2) core-shell nanophosphors were characterized by transmission electron microscopy, UV/vis absorption and photoluminescence spectroscopy, energy-dispersive x-ray analysis (EDAX), selected area electron diffraction and zeta-potential measurements. The obtained nanocomposites have quite a uniform spherical shape and diameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Recently, YAG:Ce [38], LaPO 4 :Eu [75]; CePO 4 :Tb [75]; YVO 4 :Eu [14,74]; and (Y,P)VO 4 :Eu,Bi [19] nanoparticles <20 nm in size have been produced.…”
Section: Nanophosphorsmentioning
confidence: 99%
“…Recently, YAG:Ce [38], LaPO 4 :Eu [75]; CePO 4 :Tb [75]; YVO 4 :Eu [14,74]; and (Y,P)VO 4 :Eu,Bi [19] nanoparticles <20 nm in size have been produced.…”
Section: Nanophosphorsmentioning
confidence: 99%
“…D 2d site is highly asymmetric leading to the high electric dipole transition probability. In free VO 4 3− , the charge transfer from oxygen ligands to the central vanadium shows maximum absorption at 268 nm [27]. From the viewpoint of molecular orbital theory, it corresponds to transitions from the 1 A 2 ( 1 T 1 ) ground state to 1 A 1 ( 1 E) and 1 E ( 1 T 2 ) excited states of VO 4 3− ion.…”
Section: Photoluminescence Studymentioning
confidence: 99%
“…Many works on improvement of luminescent properties of core-shell nanoparticles such as SnO 2 :Eu-TiO 2 , SnO 2 :Eu-SiO 2 , LaF 3 :RE-LaF 3 and YVO 4 :Eu-SiO 2 were reported [15,27,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…To alleviate the impact of surface defects in nanocrystalline powders, core/shell structured nanoparticles have been used to stabilize the surface of the nanoparticles. 54,55 It was found that the luminescence intensity, chemical stability and thermal stability were improved by the presence of inert shells. [56][57][58] It has been found that EPD from suspension of nano-sized particles of (Ba 0.97 Eu 0.03 ) 2 SiO 4 in an IPA bath yielded a non-uniform and porous film, 28 as shown in Figure 15, for both photographs (under excitation of 365 nm light) and SEM micrographs.…”
Section: Ecs Journal Of Solid State Science and Technology 5 (1) R31mentioning
confidence: 99%